Simulated Annealing Algorithm for the Weighted Unrelated Parallel Machines Problem - Cruz-Chavez, M.A.; Juarez-Perez, F.; Avila-Melgar, E.Y.; Martinez-Oropeza, A. (CERMA 2009 : 2009 Electronics, Robotics and Automotive Mechanics Conference : proceedings, 22-25 September 2009, Cuernavaca, Morelos, Mexico, 2009)
In this paper, a solution is presented to the unrelated parallel machines problem that minimizes the total weighted completion time. Simulated annealing is applied to the problem, which is modeled as a weighted bipartite matching problem. Experimental results with benchmarks are presented, evaluating the efficiency and efficacy of the algorithm. It is then compared with an exact algorithm that solves the pondered model of integer linear programming. The results demonstrate that simulated annealing algorithm has high performance because for all the evaluated instances, it finds the optimum global solution.